Seminar Strategi Inovatif Menghadapi Persaingan Dunia Kerja Siswa SMK Al-Ishlah - Sarmin Sarmin; Soedjatmoko Soedjatmoko; Ahmad Fauzi; Nurul Toyyibatun Hasanah; Toyib Toyib; Zubair Awali; Diana Novita (Lembaga Pengembangan Kinerja Dosen, 2026)
In today's competitive digital era, an individual's success is not only determined by technical skills but also by the ability to build relationships (networking), manage time effectively (time management), and create a strong personal image (personal branding). This seminar activity was conducted on Saturday, October 25, 2025, at SMK Al-Ishlah North Cikarang. The participants of this seminar were 41 students from grades X and XI. In this activity, participants were given a pretest and posttest to measure their understanding and feedback to assess the success of the seminar event. After receiving the pretest, participants were provided with material on innovative strategies for facing competition in the job market, namely Networking, Time Management, and Personal Branding. Based on the data from the pretest and posttest, the average participant showed an increase in understanding of 72.69%.The community service team hopes that the students of SMK Al Ishlah will be able to more easily face the competition in the job market and achieve their aspirations in the future.